Refining the theoretical construct of Islamic work ethic: A qualitative study / Siti Fairuz Ramlan - Siti Fairuz , Ramlan (2017)
Islamic work ethic is initially developed as an orientation for the Muslim society to address the lack of sound management and decline in economic growth. The Islamic work ethic has been a subject of interest, especially in the wake of the Islamization of knowledge. Many scholars have attempted to conceptualize Islamic work ethic, including Abbas J. Ali, who developed the scale of Islamic work ethic. While the growing number of studies established Islamic work ethic as an emerging field of research, the conceptualization of Islamic work ethic appears to be segmented and divided to philosophical, managerial and psychological. To address this issue, this research seek to develop the theoretical construct of Islamic work ethic based on these three main objectives: to examine the content of classical and contemporary works of Islamic work ethic, to evaluate the scholarly works in developing the initial construct of Islamic work ethic and to refine the initial construct of Islamic work ethic based on expert validation. The research uses qualitative approaches in the process of data collection; documentation and in-depth interview. The classic and contemporary works of Islamic work ethic are examined to understand the scholarly theories and concepts related to Islamic work ethic. These works are analysed using constant comparative method to identify the five points of similarity and two points of difference. These comparative points are used to develop the initial construct which consist of five elements; principle, objectives, sources, scopes and core values. The initial construct is validated by a panel of experts, which consist of nine respondents from academic and industrial background. The interview finding is analysed thematically to refine the initial construct and consequently, produce the final construct of Islamic work ethic. It is discovered that the final construct does not differ much from the initial construct. The original five elements is retained in the construct with some modification on the content of the element. It is hoped that this final theoretical construct have successfully harmonized the distinguished thoughts and theories on Islamic work ethic, as well as to generate a holistic conceptualization on Islamic work ethic as the groundwork for future studies in various fields of knowledge.